2021
DOI: 10.3389/fnhum.2021.636472
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamic Amplitude of Low-Frequency Fluctuations in Patients With Migraine Without Aura

Abstract: Migraine is a chronic and idiopathic disorder leading to cognitive and affective problems. However, the neural basis of migraine without aura is still unclear. In this study, dynamic amplitude of low-frequency fluctuations (dALFF) analyses were performed in 21 patients with migraine without aura and 21 gender- and age-matched healthy controls to identify the voxel-level abnormal functional dynamics. Significantly decreased dALFF in the bilateral anterior insula, bilateral lateral orbitofrontal cortex, bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…One recent rs-fMRI study of chronic migraine revealed disrupted negative FC between DMN and CC of patients [51]. Another study investigated migraine brain using dynamic amplitude of low-frequency uctuations (dALFF) also found decreased dynamics in both DMN and CC [53]. In the present study, the higher occurrence of a state with obvious FC between DMN and CC may indicate that state as a neural substrate for the dysregulation of static FC between networks in CTN.…”
Section: Increased Reoccurrence Fraction In Statesupporting
confidence: 59%
“…One recent rs-fMRI study of chronic migraine revealed disrupted negative FC between DMN and CC of patients [51]. Another study investigated migraine brain using dynamic amplitude of low-frequency uctuations (dALFF) also found decreased dynamics in both DMN and CC [53]. In the present study, the higher occurrence of a state with obvious FC between DMN and CC may indicate that state as a neural substrate for the dysregulation of static FC between networks in CTN.…”
Section: Increased Reoccurrence Fraction In Statesupporting
confidence: 59%
“…The medial orbitofrontal, as the key node in the DMN, is involved in the cognitive aspects of pain processing and top-down modulation of pain ( Schwedt et al, 2015 ). Our results provide more detail on the DMN anomaly hypothesis of migraines ( Tessitore et al, 2013 ; Zou et al, 2019 ; Chen et al, 2021 ) and that these abnormalities vary over time in migraineurs. The postcentral gyrus, paracentral lobule, and parietal gyrus are important parts of the sensorimotor network ( Quairiaux et al, 2011 ), which is closely related to pain and is the main pain-regulating central system ( Bornhovd et al, 2002 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 56%
“…Traditionally, brain dynamic activity has been mainly explored based on measuring the mean or variance of the sequence ( Chen et al, 2021 ; Lim et al, 2021 ) in a single time scale. These methods often overlooked the importance of the interaction among numerous neuronal circuits over a wide range of temporal and spatial scales, which is the basis of the brain to adapt to the ever-changing environment and to perform various mental functions ( Yang et al, 2015 ; Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One recent rs-fMRI study on chronic migraine revealed disrupted negative FC between the DMN and CC of patients [ 58 ]. Another study investigated the migraine brain using dynamic amplitude of low-frequency fluctuations (dALFF) and found decreased dynamics in both DMN and CC [ 60 ]. In the present study, the higher occurrence of a state with obvious FC between DMN and CC may indicate the state is a neural substrate for the dysregulation of static FC between networks in CTN.…”
Section: Discussionmentioning
confidence: 99%